THEORETICAL AND CONCEPTUAL FOUNDATIONS FOR INTEGRATING ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION (Uzbekistan Open Conference, 2026)
This article examines the theoretical and conceptual foundations necessary for integrating artificial intelligence (AI) technologies into higher education. As AI continues to transform the field of education, understanding the core theoretical constructs is critically important for effective implementation. This study explores the key pedagogical theories, learning processes, and systematic approaches that support the integration of artificial intelligence in a university environment. The research identifies critical factors influencing the successful adoption of artificial intelligence, including constructivist learning theory, adaptive learning models, and institutional readiness methods. The results indicate that a comprehensive theoretical foundation combining educational psychology, technology acceptance models, and organizational change theory is essential for sustainable AI integration in higher education institutions.